Right To Self-Determination and Indian Constitution: An Analysis: A Historical and Legal Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2021)
All peoples have the right of self-determination. By virtue of that right they freely determine their political status and freely pursue their economic, social and cultural development. Right to self-determination states that “people, based on respect for the principle of equal rights and fair equality of opportunity, have the right to freely choose their sovereignty and international political status with no interference” The right to self-determination is a basic and important right constituted in the International law. Public participation is essence of democracy. Without self-governance, there is no possibility of real public participation and therefore democracy loses its authenticity without exercising this right. If we look at the historical evolution of this legal right, it has different origins in historical sense. Before the Second World War that is prior to the establishment of U.N and adoption of the U.N charter, right to self-determination wasn’t considered as legal right under the international framework. It was first expressed in 1860’s and gained attention after that. The two individuals Vladimir Lenin and U.S President Woodrow Wilson significantly contributed towards the emergence of the principle of self-determination at international level. Wilson stated “National aspirations must be respected people may now be dominated and governed only by their own consent. So to save democracy we all must take initiatives to protect the right of self-determination.